Quantum aspects of solitons and deformations on Ad'S IND. 4'x C'P POT.3' ('S POT. 7') - López-Arcos, Christhiam Manuel [UNESP] (2014)
In this thesis we will analyze two problems for backgrounds of the type AdS4 × M. In the ﬁrst part, we will discuss the ambiguities in the computation of the 1-loop correction for the energy of spinning strings on AdS4 ×CP3, using a method that solved the problem on the four dimensional kink in ﬁeld theory. In the second part we will study the deformation of a black hole in AdS4 ×S7, and use a membrane paradigm-like calculation to obtain the conductivity on the Ginzburg-Landau model via the AdS-condensed matter duality (AdS/CMT), that has been recently developed.